Perfil do consumidor de queijos na cidade de Dom Pedrito - RS - Cunha, Paola Tristão da (2016)
The cheese consume and production comes from ancient times, when the animals began to be domesticated and was found that the milk could be transformed naturally into a derivated product with an interesting flavor to taste. Through the years the production of this derivated products had been improved, developing products that delight the most refined as well as the simplest taste of consumers to introduce it in the daily alimentation. This paper was realized in the city of Dom Pedrito - RS, to identify the cheese consumer’s profile and the acceptance of three types of cheese. It had been concluded 76 survey questionnaires, with multiple choice answers about consume habits and consumer’s preference. After frequency analisys were found that 97,3% of the interviewed answered they consume cheese where 43,4% of them consume cheese daily and don’t need special occasions to consume it. Regarding to sheep milk cheese, 44,7% of the participants had already consumed this derivated product, from them 76,4% liked too much and 23,5% liked the product when tasted it. Concerning the types of cheese offered in the tasting session, 47,3% preferred the sample 1 which was gouda, 30,2% preferred the sample 2 which was samsoe and 22,36% preferred sample 3 which was feta made with sheep milk, inferring that still exist a kind of opposition in the consumer’s taste about the type of sheep milk cheese offered.